2006
DOI: 10.1002/em.20202
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced DNA damage and repair in peripheral blood mononuclear cells from Nijmegen breakage syndrome patients and carriers assessed by the Comet assay

Abstract: Nijmegen breakage syndrome (NBS) patients and carriers are predisposed to malignancy and are often treated with X-irradiation. In the present study, the single-cell gel electrophoresis (Comet) assay was used to examine radiation-induced DNA damage and repair in peripheral blood mononuclear cells from NBS patients (n=13) and carriers (n=36) of six unrelated families. Cells from apparently healthy donors (n=10) and from breast cancer patients with normal clinical radiosensitivity (n=10) served as controls. Cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 46 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The Comet assay was performed under alkaline conditions following a protocol reported elsewhere (21,22). DNA fragmentation was quantified from the 'Tail Moment' (TM, given in arbitrary units, a.u.…”
Section: Cellsmentioning
confidence: 99%
“…The Comet assay was performed under alkaline conditions following a protocol reported elsewhere (21,22). DNA fragmentation was quantified from the 'Tail Moment' (TM, given in arbitrary units, a.u.…”
Section: Cellsmentioning
confidence: 99%
“…Bu¨rger et al 8 in a study of six Nijmegen breakage syndrome families using peripheral blood mononuclear cells found that two out of the six families were more sensitive to X-irradiation than the controls. DNA repair was also reported to take longer in four out of the six families, while cells from five families with the syndrome had significantly increased residual DNA damage following repair.…”
Section: Clinical Studiesmentioning
confidence: 98%
“…In a study of patients with Cockayne syndrome (CS), a mutation in the repair pathway gene ERCC6 did not impair genetic reprogramming but exhibited elevated cell death rates and ROS production 25 . As NBS cells are hypersensitive to DNA damage 26 , ROS may be detrimental to them under physiological conditions. Thus, it was hypothesized that antioxidants or the induction of pluripotency in NBS fibroblasts might suppress and maybe bypass ROS-mediated genome instability.…”
Section: Introductionmentioning
confidence: 99%